PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PENJUALAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fista, Bela Febriana; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTHigh firm value has become the desire of the owners of the company, because high value reflects the prosperity ofthe shareholders as well, and the management company should strive to maximize the prosperity ofshareholders. This research is aimed to find out the influence of dividend policy, sales growth, profitability andfirm size to the firm value. The population is go public telecommunication companies which are listed inIndonesia Stock Exchange, the sample collection techniques has been done by using purposive sampling and thesamples are 5 companies, and the observations period in 2011-2015. The data is the secondary data usingfinancial statement data. The analysis technique has been carried out by uising multiple linear regressionanalysis. The result of this research uses model feasibility test shows that the models are feasible to be used forthe following research, and the hypothesis test has been done by using t-test shows that dividend policy, salesgrowth, profitability and firm size give significant and positive influence to the firm value.Keywords: Dividend policy, sales growth, profitability, company size, the value of the company